2021
DOI: 10.3389/fendo.2021.609470
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus and COVID-19: A Narrative Review

Abstract: The pandemic of coronavirus disease (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has involved more than one hundred million individuals, including more than two million deaths. Diabetes represents one of the most prevalent chronic conditions worldwide and significantly increases the risk of hospitalization and death in COVID-19 patients. In this review, we discuss the prevalence, the pathophysiological mechanisms, and the outcomes of COVID-19 infection in people with diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 92 publications
1
61
0
3
Order By: Relevance
“…[66]. Likewise, it has been demonstrated that there is a critical relationship between cytokine storms and morbidity in patients with SARS-CoV and MERS-CoV [67]. Furthermore, elevated levels of IL-6, a hallmark of severe MERS-CoV infection, is common in COVID-19 patients with respiratory failure and ARDS.…”
Section: Diabetes Covid-19 and Immune Responsementioning
confidence: 99%
“…[66]. Likewise, it has been demonstrated that there is a critical relationship between cytokine storms and morbidity in patients with SARS-CoV and MERS-CoV [67]. Furthermore, elevated levels of IL-6, a hallmark of severe MERS-CoV infection, is common in COVID-19 patients with respiratory failure and ARDS.…”
Section: Diabetes Covid-19 and Immune Responsementioning
confidence: 99%
“…This condition of inflammatory interrupts the regulation of homeostatic glucose and peripheral insulin sensitivity. An abnormal and ineffective immune response can determine chronic hyperglycemia and inflammation [ 14 , 15 ]. Besides, recent studies have shown that patients with diabetes and severe COVID-19 showed a severe inflammatory response and were more likely to get mechanical ventilation and have higher mortality compared to non-diabetics [ [16] , [17] , [18] , [19] ].…”
Section: Why Diabetes Is Important?mentioning
confidence: 99%
“…The study also revealed that individuals with diabetes showed a much higher death rate (20.5 % versus 12.3 %) and lower survival time than patients without diabetes [ 27 ]. Further, another study done with 300 adult patients carrying confirmed SARS-CoV2 infection and hospitalized at King Salman Hospital from May 1 to July 31, 2020, showed T2D as the most typical comorbidity in 45.7 % of those affected with COVID-19 disease [ 15 ]. A study conducted among 566 patients at Security Forces Hospital in Riyadh, Saudi Arabia, between March 15 and June 30, 2020, showed that the most common comorbidity was diabetes (21.8 %; 123/566) [ 39 ].…”
Section: Why Diabetes Is Important?mentioning
confidence: 99%
“…Hypertension should consider as a clinical predictor for the severity of COVID-19 both in adults and children [10]. Also, diabetes is another comorbidity to increase the COVID-19 disease burden and mortality worldwide [11,12]. It plays a primary role in the development of pneumonia and sepsis due to the virus infection.…”
Section: Introductionmentioning
confidence: 99%